SOSIALISASI PENCEGAHAN HIV PADA REMAJA DI SAMARINDA - Wahid, Rifky Saldi A.; Raudah, Siti (Jurnal Pengabdian Masyarakat Teknologi Laboratorium Medik Borneo, 2022)
HIV/AIDS (Human Immunodeficiency Virus/Acquired Immuno Deficiency Syndrome) is the biggest health problem in the world today, including in Indonesia. The growing problem associated with HIV/AIDS infection is that the incidence rate tends to increase with a high mortality rate. The HIV virus is found in body fluids, especially blood, semen, vaginal fluids, and breast milk. This virus destroys the immunity of the human body and causes a decrease in the body's resistance so that it is easily exposed to infectious diseases. The incidence of HIV/AIDS is more prone to occur in adolescence. Where the emotional state is still unstable and the desire to try new things is very high. This activity is carried out by analyzing the results of research and explaining community service plans, this community service activity is a PowerPoint media in counselling. Regarding the Prevention of Human Immunodeficiency Virus (HIV) in adolescents in Samarinda by conducting counselling on Human Immunodeficiency Virus (HIV) and its prevention. The results obtained from this community service activity, the students participated in this health education activity with high enthusiasm and enthusiasm which was shown by a cheerful and conducive atmosphere during the activity. Most of the participants began to understand the Human Immunodeficiency Virus (HIV) and its prevention. And students' knowledge to carry out a healthy lifestyle, diet and unsafe sex in adolescent reproductive health can be implemented as one of the preventions of Human Immunodeficiency Virus (HIV).